Prevalence and risks for bacterial vaginosis in women who have sex with women - Marrazzo, Jeanne M; Thomas, Katherine K; Agnew, Kathy; Ringwood, Kathleen (Sexually transmitted diseases, 2010)
Bacterial vaginosis (BV) is a common cause of vaginitis and, for unknown reasons, is common in lesbian and bisexual women. We defined risks for prevalent BV in lesbian and bisexual women with attention to detailed sexual risk history. Women 16 to 35 years reporting sex with > or = 1 woman in prior year underwent computer-assisted self-interview with extensive sexual and medical history. BV was defined by Amsel criteria, and associations with subject characteristics were estimated by Poisson regression and generalized estimating equation to adjust for potential coenrollment of current sexual partners. Of 335 participants (median age, 25 years; 22% nonwhite race), 6% reported douching, 24% sex with men, and 91% any sex in the prior 3 months. 96 (29%) had BV, 40% of whom reported corresponding symptoms. BV was associated with reporting a partner with BV (39% vs. 12%; multivariate relative risk [MRR], 4.53 [2.59 -7.93]), vaginal lubricant use (59% vs. 21%; MRR, 1.86 [0.94 -3.68]), or sharing vaginal sex toys in prior 3 months (33% vs. 21%; MRR, 1.70 [0.96 -3.01]). No association was seen for age, race, smoking, hormone use, douching, vaginal, anal or oral sex, or numbers of new partners. Lubricant use and shared vaginal toys were correlated (Spearman 0.29). BV is associated with practices that efficiently transmit vaginal fluid and with use of vaginal lubricant; since these are correlated, assessing independent effects will require further analysis. More research is required to understand relationships between role of transmission of BV-associated bacteria and vaginal lubricant on BV pathogenesis.